Comparative study on annealing‐induced high‐impact toughness of linear and grafted polypropylene random copolymer. (19th January 2023) - Liu, Jingru; Lu, Bingkun; Xiao, Rui
Abstract: In present work, the comparative study on annealing‐induced high‐impact toughness of linear and grafted polypropylene random copolymer (PPR and MPP) was performed. The changes of microstructure and mechanical properties of PPR and MPP upon annealing were investigated in detail. The results showed that maleic anhydride was grafted onto the backbone of PPR to form long‐chain branched structure. During the melt grafting process, the degradation reaction is dominant, giving rise to the decrease in molecular weight and degree of chain entanglement, and hence PPR demonstrates higher flexural modulus and impact strength, as well as lower elongation at break than MPP. The long‐branched chains perform the function of heterogeneous nucleation. The depressed chain entanglement facilitates the diffusion of polymer chains during the crystallization process, followed by higher total crystallization rate and crystallinity of MPP in contrast to those of PPR. Thermal annealing treatment promotes the secondary crystallization, and hence the crystallinity and crystal perfection of the polymer is elevated, resulting in enhanced mobility of the chain segments in the amorphous region. After annealing at 100°C for 3 h, the impact strength of MPP is 71% higher than that of its unannealed counterpart, while this value is increased remarkably by 153% for PPR. The existence of long‐branched chains may not be conducive to sufficient rearrangement of chain segments of MPP during the annealing treatment. As a consequence, the crystallinity and impact strength of PPR are elevated more pronouncedly in comparison with those of MPP after annealing treatment.